Các hợp chất đitecpenoit phân lập từ quả loài na biển (Annona glabra) (Phần 2) - Kiệm, Phan Văn; Thu Hiền, Nguyễn Thị; Thúy Hằng, Đan Thị; Dung, Dương Thị; Cúc, Nguyễn Thị; Hải Yến, Dương Thị; Tuấn Anh, Hoàng Lê; Nhiệm, Nguyễn Xuân; Minh, Châu Văn (Vietnam Journal of Chemistry, 2015)
Four ent-kaurane diterpenoids, annoglabasin E (1), annonaglabasin B (2), 19-nor-ent-kauran-4α-ol-17-oic acid (3), and paniculoside IV (4) were isolated from the methanol extract of the Annona glabra fruits by various chromatographic experiments. Their structures were characterized by 1D- and 2D-NMR spectra and ESI-MS, as well as in comparison with those reported in the literature. Among these compounds, 4 has been isolated from the genus Annona for the first time.